Deconstructing substitution narratives: the case of bioeconomy innovations from the forest-based sector - Giurca, Alexandru; Befort, Nicolas (Ecological economics, 2023)
Under the European Union's bioeconomy strategy, wood-based bioeconomy innovations are expected to produce a stream of marketable substitutive products (lignin-based products, textiles, polymers, chemicals, oils, construction materials, etc). By analyzing how different actors frame substitution, this article advances our theoretical understanding of the drop-in vs functional-innovations (DIFI) framework and critiques the current innovation trajectory that the forest-based sector has embarked upon. The proposed approach sheds light on the role that actors attribute to innovation in the bioeconomy by linking the question of expectations with technological promises and bioeconomy imaginaries. In this respect, this discussion is of relevance for bioeconomy innovation scholars, policymakers, and entrepreneurs seeking to go beyond the current “substitution is the solution” storyline of the forest industry and instead, help shape bioeconomy innovations that have the potential to bring about sustainable and transformative change.